2019
DOI: 10.1038/s41598-019-41818-6
|View full text |Cite
|
Sign up to set email alerts
|

Ti2NiCoSnSb - a new half-Heusler type high-entropy alloy showing simultaneous increase in Seebeck coefficient and electrical conductivity for thermoelectric applications

Abstract: A new single phase high entropy alloy, Ti 2 NiCoSnSb with half-Heusler (HH) structure is synthesized for the first time by vacuum arc melting (VAM) followed by ball-milling (BM). The BM step is necessary to obtain the single phase. Local electrode atom probe (LEAP) analysis showed that the elements are homogeneously and randomly distributed in the HH phase without any clustering tendency. When the BM was carried out for 1 hour on the VAM alloy, microcrystalline alloy is obtained with tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
77
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 41 publications
3
77
1
Order By: Relevance
“…From the material functionality perspective, it is plausible to “define” HEA as a material that exhibits these four core effects: high configurational entropy, sluggish atomic diffusion, severe lattice distortions, and the cocktail effect. These core effects of HEA are well aligned with the material requirements for good thermoelectrics 33–40. Specifically, high configurational entropy elicits: i) extended solubility limits of specific elements and high‐symmetry crystal structure, thereby expanding the phase space for performance optimization and favoring good electronic band structure; ii) severely distorted crystal lattice, thereby softening and impeding heat‐carrying phonons; and iii) slow diffusion processes, thereby creating rich multiscale microstructures prerequisite for reducing the lattice thermal conductivity.…”
Section: Introductionmentioning
confidence: 79%
“…From the material functionality perspective, it is plausible to “define” HEA as a material that exhibits these four core effects: high configurational entropy, sluggish atomic diffusion, severe lattice distortions, and the cocktail effect. These core effects of HEA are well aligned with the material requirements for good thermoelectrics 33–40. Specifically, high configurational entropy elicits: i) extended solubility limits of specific elements and high‐symmetry crystal structure, thereby expanding the phase space for performance optimization and favoring good electronic band structure; ii) severely distorted crystal lattice, thereby softening and impeding heat‐carrying phonons; and iii) slow diffusion processes, thereby creating rich multiscale microstructures prerequisite for reducing the lattice thermal conductivity.…”
Section: Introductionmentioning
confidence: 79%
“…Electrons scattering in highentropy systems can be exacerbated because of high lattice distortion, which has been used to reduce electronic thermal conductivity in thermoelectric materials. As specific tests on electrical properties of HEAs are seldom conducted [91,100,101,102], electrical conductivity is often a property measured to characterize the thermoelectrical performance of materials [86,87,89,103]. The synthesis routes and compositions of NC HEAs can significantly affect their electrical properties.…”
Section: Electrical Conductivitymentioning
confidence: 99%
“…As one of the proposed "core" effects in HEAs, severe lattice distortion can affect not only electron movement but can also drive phonon scattering and, therefore, reduce thermal conductivity [104]. Such an effect makes HEAs a promising class of potential high-performance thermoelectric materials, attracting significant research interest recently [103,105]. In general, it has been recognized that the two most efficient ways of improving thermoelectric performance are (i) modifying a material's electronic/thermal transport properties and (ii) maintaining crystal symmetry for higher Seebeck coefficients.…”
Section: Thermal Conductivity and Thermoelectric Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports proved that Half Heusler (HH) alloys also shows the thermoelectric property owing to presence of 18 electrons in valence shell and the position of Fermi-level (E F ) lies above-occupied valence shell that would results in better semiconducting behaviour. Wu et al [12,13] observed the thermoelectric behaviour in TiCoSb Half-Heusler which generally exhibits n-type conduction and tried to tune n-type behaviour to p-type by substitution of Ge by Sb and found the enhanced thermoelectric properties from room temperature to 880 K. Makongo et al [14] presented the thermoelectric and electronic transport behaviour of bulk nanostructured Zr 0.25 Hf 0.75 NiSn composites containing various mole fraction of Full-Heusler inclusions. Moreover, the formation of coherent phase from Full Heusler inclusions (FH) into the…”
mentioning
confidence: 99%